Given the system of equations :
![\begin{gathered} 2x+5y=-49 \\ -2x+8y=-68 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dvdbbbsm70pkg27iwmxa912xyf02m050vn.png)
Add the equations to eliminate x :
![\begin{gathered} (2x+5y)+(-2x+8y)=-49+(-68) \\ 2x+5y-2x+8y=-117 \\ (2x-2x)+(5y+8y)=-117 \\ 13y=-117 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/h40qe6a2iot1zx8v7ixx6uzszpm2c6ugx5.png)
divide both sides by 13 to find the value of y :
![\begin{gathered} (13y)/(13)=(-117)/(13) \\ \\ y=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dsfy2rgmtkowa8e7qj8m9pytyb76zlv9jh.png)
To find x , substitute with the value of y at the first equation :
![\begin{gathered} 2x+5\cdot-9=-49 \\ 2x-45=-49 \\ 2x=-49+45 \\ 2x=-4 \\ \\ x=-(4)/(2) \\ \\ x=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8tj7kdpsuhp4ar8byyhqhnbecw584wf0gs.png)
So, the solution of the system is :
![\begin{gathered} x=-2 \\ y=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/n7wz4oxh4q58p8fu4ovhrhey9zr8o12bsx.png)
The solution can be written as the order pair (x,y):
![(x,y)=(-2,-9)](https://img.qammunity.org/2023/formulas/mathematics/high-school/gl173l0ym7klxm4hfsssnoggnrq6564rcd.png)